N-(2-Nitrophenylsulfonyl)-N-(4-nitrophenylsulfonyl)methylamine - Haiyan Lu (Acta Crystallographica Section E, 2008)
In the crystal structure of the title compound, C13H11N3O8S2, molecules are linked by intermolecular C—H...O hydrogen bonds into zigzag chains running parallel to the c axis. Centrosymmetrically related chains are further stabilized by aromatic π–π stacking interactions [centroid–centroid distance = 3.749 (3) Å] involving adjacent 4-nitrobenzene rings. Intramolecular C—H...O hydrogen bonds are also present.